2001
DOI: 10.1055/s-2001-14320
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers as a Tool to Verify Sexual and Apomictic Off-Spring of Intraspecific Crosses in Hypericum perforatum

Abstract: The aim of this project was to establish RAPD markers to determine the percentage of sexual off-spring of the facultative apomictic plant species H. perforatum. We did reciprocal crosses between four different accessions (A x B, B x A, C x D, D x C) by mechanical emasculation and hand pollination. Genomic DNA of the parents and the off-spring was isolated and PCR conditions were optimized in order to obtain reproducible bands with RAPD markers. Of the 260 screened RAPD primers 127 revealed polymorphism between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Interspecific hybridization has been recently reported but its consequences on the polyphenolic profile of SJW has not been evaluated so far. On this regard some RAPD based methods to precisely verify intraspecific crossings during hybrid selection are becoming available and could be helpful during the breeding process [ 155 ]. Comparative breeding and long-term selection of lines evaluated not simply for their agronomic advantages (gross yield, resistance, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific hybridization has been recently reported but its consequences on the polyphenolic profile of SJW has not been evaluated so far. On this regard some RAPD based methods to precisely verify intraspecific crossings during hybrid selection are becoming available and could be helpful during the breeding process [ 155 ]. Comparative breeding and long-term selection of lines evaluated not simply for their agronomic advantages (gross yield, resistance, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This latter study identified 11 different mechanisms of seed formation, in addition to low numbers of obligate sexually and apomictically reproducing plants: embryos of sexual origin were mainly diploid (2n ¼ 2x ¼ 16), while apomictically formed embryos were tetraploid (2n ¼ 4x ¼ 32) or hexaploid (2n ¼ 6x ¼ 48). The different modes of reproduction in this species have been confirmed numerous times by examining molecular marker segregation in maternal plants and their progenies (Halušková and Č ellárová, 1997;Arnholdt-Schmitt, 2000;Steck et al, 2001). DNA fingerprinting techniques in conjunction with cytological investigations have furthermore demonstrated low frequencies of recombinant offspring from otherwise apomictic mother plants (Halušková and Košuth, 2003;Mayo and Langridge, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…H. perforatum is considered to be a facultative, pseudogamous, apomictic plant (Mayo and Langridge, 2003). Randomly amplified polymorphic DNA (RAPD) and fingerprinting and restriction fragment length polymorphism (RFLP) are used as tools for research on the mode of reproduction of this species (Haluskova and Cellarova, 1997;Arnholdt-Schmitt, 2000;Steck et al, 2001). This plant is thought to be of allopolyploid origin (Martonfi et al, 1996) and most commonly occurs as a tetraploid (2n ¼ 4x ¼ 32) (Nielsen, 1924;Brutovska et al, 2000).…”
Section: Classicalmentioning
confidence: 99%